Time course of the effects of static stretching on cycling economy - Wolfe, A. E.; Brown, L. E.; Coburn, J. W.; Kersey, R. D.; Bottaro, M. (The Journal of Strength and Conditioning Research, 2011)
Stretching has been implemented as part of the warm-up before physical events and widely thought to promote increased sport performance and decreased injury risk. However, recent research has concluded that static stretching before many exercises inhibits acute power, strength, and sprinting performance. There is little research examining the time course of these effects on moderate intensity cycling. The purpose of this study was to examine the time course of static stretching on cycling economy. The subjects consisted of 5 men and 5 women highly trained endurance cyclists. The first of 3 visits was baseline testing of their cycling VO2max. The second and third visits were either stretching or no stretching before a 30-minute stationary ride at 65% of their VO2max. The stretching condition consisted of four 30-second repetitions of 5 stretches with an average total stretching time of 16 minutes. VO2 demonstrated a significant condition by time interaction with the 5-minute time point being significantly less in the nonstretching condition (32.66 ± 5.35 ml/kg/min) than stretching (34.39 ± 5.39 ml/kg/min). No other time points were different. Our results demonstrate that static stretching yielded an acute increase in submaximal VO2; therefore, coaches and highly trained endurance cyclists should exclude static stretching immediately before moderate intensity cycling because it reduces acute cycling economy.